Silent Film Music Research as Local Musicology: A Case Study of Musical Practices and Networks in Ottawa Theatres from 1897 to 1929 - Marshall, Elsa (Université d'Ottawa / University of Ottawa, 2017)
The Basilica Notre-Dame Choir accompanying screenings of The Hunchback of Notre Dame at the Regent in 1924, imaginative community prologues before Mary Pickford’s Pollyanna at the Russell in 1920, and costumed opera soloists singing alongside the showing of The Bohemian Girl at the Imperial in 1926: the history of Ottawa’s silent cinemas is an exciting mix of film, theatre, technology, music, and community. Unfortunately, Ottawa’s musical history in the early 1900s has been, by and large, forgotten, and local cinema histories are relatively sparse. In much the same manner that Ottawa theatres incorporated both North American and local elements into their programming, this thesis demonstrates that an examination of the musicians of local cinemas can not only provide information to understand the development of silent film music practices in general, but also unveil a network of musicians and a series of important histories. This thesis reconstructs parts of Ottawa’s silent film music history using a number of methodologies (digital research, archival research, and social network mapping) and primary sources (IATSE union documents, Department of Labour strike documents, newspapers, and trade journals). It also analyses several screenings where music and film were uniquely combined and introduces key figures in Ottawa’s silent film music scene (including violinist Rudolph Pelisek and organist Amédée Tremblay), showing how their training provided prestige to cinemas and how their involvement in military, religious, and communal activities added to cinemas’ appeal. ----- Le Chœur de la Basilique Notre-Dame accompagnant les présentations du film The Hunchback of Notre Dame au Regent en 1924, les prologues communautaires inventifs avant le Pollyanna de Mary Pickford au Russell en 1920, et les soloistes d’opéra chantant à côté de la projection de The Bohemian Girl à l’Imperial en 1926: l’histoire des cinémas muets d’Ottawa est un mélange excitant de film, théâtre, technologie, musique et communauté. Malheureusement, le passé musical d’Ottawa au début du vingtième siècle a été largement oublié, et les histoires locales du cinéma sont relativement rares. De la même façon que les théâtres d’Ottawa incluaient à la fois des éléments locaux et nord-américains dans leur programmation, cette thèse démontre qu’un examen des musiciens des cinémas locaux peut non seulement procurer des renseignements pour comprendre le développement de la musique du cinéma muet en général, mais encore lever le voile sur un réseau de musiciens et une série de récits d’importance. Cette thèse reconstruit des aspects de l’histoire de la musique du du cinéma muet à Ottawa en utilisant un plusieurs méthodologies (la recherche numérique, la recherche en archives, et la cartographie des réseaux sociaux) et de sources primaires (documents du syndicat ouvrier IATSE, documents de grève du ministère fédéral du Travail, quotidiens, et revues spécialisées). La thèse analyse aussi quelques instances uniques de combinaison de musique et de film, et présente des personnages clé de la scène musicale du cinéma muet d’Ottawa (incluant le violoniste Rudolph Pelisek et l’organiste Amédée Tremblay), tout en montrant comment leur formation procurait du prestige aux cinémas, et comment leur implication dans des activités militaires, religieuses, et communautaires ont ajouté à la popularité des cinémas.
Keywords: Silent Film Music; Silent Film; Musicology; Local History; Film Music; Ottawa; Ontario; Canada; Historical Musicology; Social Networks; Cultural Infrastructure; Theatre; Orchestra; Cinema; Film